(untitled) (Scientific journal of the Fergana State University, 2025)
Along with mineral fertilizers, harmful compounds such as fluorine, radioactive elements, as well as other compounds that are added to increase the efficiency of technology come to the soil. According to experts, 90% of arable land in our country should be fertilized with nitrogen.